2016
DOI: 10.3390/v8100263
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Study of Common Non-Nucleoside Reverse Transcriptase Inhibitor-Resistant Mutations with K103N and Y181C Substitutions

Abstract: Non-nucleoside reverse transcriptase inhibitors (NNRTIs) are a mainstay of therapy for human immunodeficiency type 1 virus (HIV-1) infections. However, their effectiveness can be hampered by the emergence of resistant mutations. To aid in designing effective NNRTIs against the resistant mutants, it is important to understand the resistance mechanism of the mutations. Here, we investigate the mechanism of the two most prevalent NNRTI-associated mutations with K103N or Y181C substitution. Virus and reverse trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Our data revealed that all of the substitutions at position Y181 (i.e., Y181C, Y181I, Y181V, and Y181F) decreased the catalytic efficiency (k pol /K d ) of RT and that these decreases were driven by both changes in K d and k pol (maximum rate of dNTP incorporation). This finding is consistent with prior reports that Y181C, Y181I, Y181V, and Y181F decrease the replicative capacity of HIV-1 (14,15). NVP, EFV, and RPV binding exerted profound effects on both nucleotide affinity and the rate of nucleotide incorporation for both the WT and mutant RT-T/P complexes (Table 4).…”
Section: Nucleotide Incorporation Reactions Carried Out By Wt and Mutsupporting
confidence: 92%
“…Our data revealed that all of the substitutions at position Y181 (i.e., Y181C, Y181I, Y181V, and Y181F) decreased the catalytic efficiency (k pol /K d ) of RT and that these decreases were driven by both changes in K d and k pol (maximum rate of dNTP incorporation). This finding is consistent with prior reports that Y181C, Y181I, Y181V, and Y181F decrease the replicative capacity of HIV-1 (14,15). NVP, EFV, and RPV binding exerted profound effects on both nucleotide affinity and the rate of nucleotide incorporation for both the WT and mutant RT-T/P complexes (Table 4).…”
Section: Nucleotide Incorporation Reactions Carried Out By Wt and Mutsupporting
confidence: 92%
“…Combinations of these mutations lead to a significant decrease in susceptibility to the inhibitor. Several particular mechanisms related to resistance to NNRTIs are described in publications [ 37 , 43 , 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…A probable mechanism leading to the resistance to RT in position Y181C and Y188L/C/H/F is associated with the loss of π - π stacking between the changed amino acids residues and small molecules [ 44 ]. The loss of antiretroviral activity in K103N mutants can be associated with several different mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…As to the K103N mutation, it was long believed that it prevented the entry of NNRTIs by stabilizing the closed conformation of NNIBP ( Hsiou et al, 2001 ). However, a more recent study indicates that the resistance is more likely caused by the electrostatic difference between Asn103 and Lys103 ( Lai et al, 2016 ). In the light of this new piece of data, the K103N mutation seems to utilize the same mechanism as Y181C and Y188L do to confer resistance to NNRTIs: by altering the shape or surface property of the NNIBP.…”
Section: Introductionmentioning
confidence: 99%